Reasoning changes of commercial sex workers in Mount Kemukus area from hedonistic to religious reasoning through moral education - Nasri Kurnialoh; Muhammad Miftah (IAIN Salatiga, 2019)
The main problem of this research is the sociological aspects of commercial sex workers (CSW) in Mount Kemukus. This study will focus on sociological forms and patterns in Mount Kemukus community from the aspect of family, social, and work environment, as well as religious activities among CSW in Mount Kemukus. This study also examines the mindset of CSW who are more inclined towards hedonistic life. As a result of this mindset, they are willing to plunge themselves into the practice of prostitution wrapped in pesugihan rituals. The forms and patterns of social interaction of CSW carried out in the sociological environment have experienced various problems, both those that are associative and those that are dissociative with the conditions in society. As for the aspects of religious activities of CSW who adhere to Islam, it shows that most of them no longer carry out the commands of Islamic teachings. One thing they know, namely the hedonist lifestyle with the fastest way to get money to meet the needs of themselves and their families, namely by working as a prostitute in the Kemukus Mountain environment.